2009
DOI: 10.2480/agrmet.65.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Applications of MODIS-visible bands index, greenery ratio to estimate CO2 budget of a rice paddy in Japan

Abstract: NDVI (Normalized Difference of Vegetation Index) was employed to estimate the carbon budget remotely with satellite data. However, NDVI has some difficulties in application to agricultural crops, boreal forest, and tundra ecosystems. We proposed a new vegetation index GR (greenery ratio) to detect the vegetation change remotely, and we applied it to estimate CO2 budget of Japanese rice paddy with MODIS satellite data. GR was ratio of green (G) to the trichromatic visible bands (R G B) of MODIS, and an empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…First, the seasonal variations in MODIS VIS_indices showed strong linear correlations with those in GPP, indicating agreement of both seasonal and interannual variations. The results supported a strong correlation between photosynthetic parameters and GR reported by Harazono et al (2009). VIS_indices are sensitive to green leaf color, so they responded to photosynthetic pigments.…”
Section: Advantages Of Visible-bands Indicessupporting
confidence: 75%
See 2 more Smart Citations
“…First, the seasonal variations in MODIS VIS_indices showed strong linear correlations with those in GPP, indicating agreement of both seasonal and interannual variations. The results supported a strong correlation between photosynthetic parameters and GR reported by Harazono et al (2009). VIS_indices are sensitive to green leaf color, so they responded to photosynthetic pigments.…”
Section: Advantages Of Visible-bands Indicessupporting
confidence: 75%
“…GR is defined as the ratio of green to the total digital numbers (R G B) of camera images (Table 1), and it can effectively detect phenological events (Ahrends et al, 2008;Maeda et al, 2008). Similarly, GR is used as the green reflectance ratio to total visible reflectance of MODIS data to estimate GPP (Harazono et al, 2009). According to the definition, GR≈1/3 indicates white or black targets such as snow, ice or soil.…”
Section: Spectral Reflectance and Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when using other VIs, GPP occasionally does not show a clear linear relationship with the products of VIs and PAR. The rate of photosynthesis and the light intensity is often nonlinear for canopies Gu et al, 2002;Saito et al, 2005 . Several studies have used GPP calculation methods with a light -response curve Furumi et al, 2005;Harazono et al, 2009;Ide et al, 2010 using satellite sensor data. However, most of them did not include the concept of the "photosynthesis capacity".…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of remote-sensing based GPP models used vegetation index (VI) data as a proxy variable for fPAR, which was assumed to have close relationship with vegetation community structure. Examples of VIs are the normalized difference vegetation index, NDVI (Rouse, 1974;Ruimy et al, 1994;Running et al, 2000;Tucker, 1979), the enhanced vegetation index, EVI (Huete et al, 2002;Xiao et al, 2005;Yan et al, 2009), the greenery ratio, GR (Harazono et al, 2009), the chlorophyll index, Chl index (Gitelson et al, 2006, and the MODIS leaf area index (LAI) product (Yuan et al, 2010). Gamon et al (1992) presented photochemical reflectance index (PRI) and found that it was correlated with the LUE of a sunflower canopy under nitrogen-stressed condition, but not under water-stressed condition.…”
Section: Review Of Remote Sensing-based Gpp Modelsmentioning
confidence: 99%